Instrumentalism and couple’s therapy: influential impacts on therapist’s values, neutrality, and perceived role in couple’s therapy - Bridges, James Gavin (Kansas State University, 2017)
Values dictate who we are, how we see the world, and how we choose to interact with others. They are imbedded in culture. Therapists and clients are dictated by values that in a large part determine the course of therapy (L’Abate, 1982). Mindful to not impose personal values on their clients, therapists may attempt what is being called a value-neutral approach, inadvertently reinforcing certain dominant cultural values about relationships that may, or may not, be in the best interest of the client’s relationship. Therapists practicing within American culture may unintentionally reinforce instrumental views of relationships in the therapy room if they attempt to remain value-neutral. The present study explored the influence of instrumentalism on therapist’s values and roles they take in therapy with two studies. Study 1 involved the construction and refining of scales that intended to measure (a) attitudes towards commitment (b) instrumentalism in romantic relationships. The attitudes towards commitment scale was created with high reliability and the instrumentalism scale was discarded and new items were created for the second study. Study 2 involved a mixed-methods approach to explore the influence of instrumentalism on therapists’ definitions and use of neutrality, as well as therapists’ roles in couple’s therapy. Participants for study 2 were sent a survey asking about demographics, relationship and commitment values, their definitions of neutrality, and the roles they take in couple’s therapy and whether they advocate more for individuals or relationships. When therapists advocate more for the relationship they are more likely to have more positive attitudes towards commitment, are less likely to endorse soft reasons for relationship dissolution, see themselves as part of a collective, and be religiously active.
Keywords: Psychotherapy; Couple's therapy; Instrumentalism; Individualism; Culture; Therapeutic neutrality